Bronchoarterial ratio in never‐smokers adults: Implications for bronchial dilation definition - Diaz, Alejandro A.; Young, Thomas P.; Maselli, Diego J.; Martinez, Carlos H.; Maclean, Erick S.; Yen, Andrew; Dass, Chandra; Simpson, Scott A.; Lynch, David A.; Kinney, Gregory L.; Hokanson, John E.; Washko, George R.; et al. (Respirology (Carlton, Vic.), 2017)
ABSTRACT Background and objective Bronchiectasis manifests as recurrent respiratory infections and reduced lung function. Airway dilation, which is measured as the ratio of the diameters of the bronchial lumen (B) and adjacent pulmonary artery (A), is a defining radiological feature of bronchiectasis. A challenge to equating the bronchoarterial (BA) ratio to disease severity is that the diameters of airway and vessel in health are not established. We sought to explore the variability of BA ratio in never‐smokers without pulmonary disease and its associations with lung function. Methods Objective measurements of the BA ratio on volumetric computed tomography (CT) scans and pulmonary function data were collected in 106 never‐smokers. The BA ratio was measured in the right upper lobe apical bronchus (RB1) and the right lower lobe basal posterior bronchus. The association between the BA ratio and forced expiratory volume in 1 s (FEV1 ) was assessed using regression analysis. Results The BA ratio was 0.79 ± 0.16 and was smaller in more peripheral RB1 bronchi (P < 0.0001). The BA ratio was >1, a typical threshold for bronchiectasis, in 10 (8.5%) subjects. Subjects with a BA ratio >1 versus ≤1 had smaller artery diameters (P < 0.0001) but not significantly larger bronchial lumens. After adjusting for age, gender, race and height, the BA ratio was directly related to FEV1 (P = 0.0007). Conclusion In never‐smokers, the BA ratio varies by airway generation and is associated with lung function. A BA ratio >1 is driven by small arteries. Using artery diameter as reference to define bronchial dilation seems inappropriate. In 106 never‐smokers adults, the mean ratio of the diameters of the bronchial lumen and adjacent pulmonary artery, a defining radiological feature of bronchiectasis, was 0.79, varied by airway generation and in 8.5% of them was >1. This metric was directly related with expiratory airflow regardless of body size.